Enhancing Word Reading Skills in Children with Speech Delay through Contextual Practice-Based Learning - Mulyani, Sri; Purwanta, Edi (Papanda Publisher, 2025)
Children with speech delays face significant challenges in developing word reading skills, which can impact their academic and social development. This study investigated the effectiveness of contextual practice-based learning methods in enhancing word reading abilities among children with speech delays in kindergarten settings. A classroom action research design following Kemmis and McTaggart's spiral model was implemented over two cycles with four children aged six years diagnosed with speech delays at TK An-Nur kindergarten, Indonesia. The intervention utilized letter dice games within contextual learning frameworks, connecting words to real-world objects and experiences. Data collection employed structured observations, performance assessments, interviews, and documentation. Assessment focused on five indicators: syllable combination, vowel and consonant recognition, letter-to-word construction, word-object association, and reading clarity with pronunciation. Significant improvements were observed across all assessment phases. Class average scores increased from 8.25 (pre-intervention) to 10.5 (Cycle I) to 13.5 (Cycle II). Mastery achievement improved from 25% to 75%, with three out of four children reaching the minimum threshold score of ≥15. Qualitative observations revealed enhanced engagement, confidence, and social participation during learning activities. Children demonstrated improved ability to connect words with concrete objects and showed increased responsiveness to verbal instructions. The contextual practice-based approach effectively addressed the specific learning needs of children with speech delays by providing meaningful, socially interactive learning experiences. Findings support Vygotsky's theoretical framework regarding the importance of social interaction and meaningful contexts in language development. The intervention's success demonstrates that accessible, low-cost methods can achieve substantial improvements in literacy development for children with developmental challenges, supporting inclusive education practices.